Evaluation of Mechanical Properties for Epoxy reinforced with palm oil /Zinc oxide composites - Hassana, Diyar J.; Ali, Nadia A. (Iraqi Journal of Physics, 2022)
In this research, the effect of reinforcing epoxy resin composites with a filler derived from chopped agriculture waste from oil palm (OP). Epoxy/OP composites were formed by dispersing (1, 3, 5, and 10 wt%) OP filler using a high-speed mechanical stirrer utilizing a hand lay-up method. The effect of adding zinc oxide (ZnO) nanoparticles, with an average size of 10-30 nm, with different wt% (1,2,3, and 5wt%) to the epoxy/oil palm composite, on the behavior of an epoxy/oil palm composite was studied with different ratios (1,2,3, and 5wt%) and an average size of 10-30 nm. Fourier Transform Infrared (FTIR) spectrometry and mechanical properties (tensile, impact, hardness, and wear rate) were used to examine the composites. The FTIR results show a strong interaction between ZnO and oil palm fiber and epoxy resin. Tensile strength was reduced from 22.78 MPa to 19.03 MPa for the epoxy/OP composite as the wt% of OP was increased but increased to 29.224MPa for epoxy /oil palm / 5% ZnO samples. Young modulus increased from 1.9 MPa to 4.3 MPa while elongation decreased (9.6 to 6.8 %) with the increase of wt% OP and ZnO. The impact and hardness increased for all composites between (6.94 - 10.8 KJ/m2) and between (80.8- 84.55 KJ/m2) respectively. Also, wear resistance of the epoxy/OP and epoxy/OP/ZnO samples increased with the increase of wt% OP and ZnO. This studied in order to provide a new step in the utilization of green nanoparticle fillers for sustainable and renewable structural products for biodegradability.